STENOKARDIA-SYMPTOMS, CAUSES, CLASSIFICATION, DIAGNOSIS, TREATMENT AND PREVENTION METHODS (The New Uzbekistan Journal of Medicine, 2025)
Angina (chest tightness) is a clinical syndrome characterized by sudden onset of myokardial ischemia and chest pain. The pain usually radiates to the left shoulder and left arm and lasts for several minutes. Three main types of angina are distinguished: 1) typical tension angina, 2) Principal angina, 3) unstable angina. Angina is a-change in heart activity caused by an imbalance between the oxygen demand of the heart muscle and blood circulation in the coronary vessels. As a result of this disorder, ischemia or necrosis is observed in the myocardium, and cardiosclerosis develops. Due to the formation of blood clots and coronary insufficiency, it manifests itself in the form of chronic recurrent, sometimes acute unstable angina pectoris or myocardial infarction.